PERSISTENCIA DE ANTICUERPOS MATERNALES CONTRA CISTICERCOSIS PORCINA Y SU EFECTO EN LA INTERPRETACIÓN DE RESULTADOS DEL EITB - Ccama S., Alberto (2003)
The study evaluate the effect of maternal antibodies against porcine cysticercosis on the interpretation of EITB test results. This data set was obtained from epidemiologic studies developed at Quilcas district, Huancayo, during a period of 4 years (1995-1998). Samples from 298 piglets and their respective dams were analized; animals were stratified by sex and immune status. Maternal antibodies persisted in the blood stream until piglets were 148.8 days old (117-242), and without significant differences between sexes. The average age in which positive piglets to EITB got infected was 170, whereas negative piglets got infected at 179.3 days of age (98-261) and without statistical differences due to sex. The immune status of piglets and dams did not interfere with age of infection. The Cox Regression showed that none of the variables under evaluation constituted a risk factor for the infection with cysticercus. This study demonstrated that maternal antibodies against porcine cysticercosis can interfere in the interpretation of results of epidemiologic studies when piglets younger than 8 month of age are sampled, probably due to the fact that the EITB test does not discriminate between material antibodies than those selfacquired as result of a natural infection.